PEMBERIAN TEPUNG DAUN SIRSAK (Annona muricata L.) DALAM MENGENDALIKAN HAMA KUMBANG BUBUK JAGUNG (Sitophilus zeamais M.) PADA BIJI JAGUNG DI PENYIMPANAN - Sembiring, Riaman; Salbiah, Desita; Rustam, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Weevil maize (Sitophilus zeamais M.) is an important pest in corn grain who are storage in warehouse. The research aims to get effective concentrations of soursop leaf powder in controlling the weevil maize (Sitophilus zeamais M.) on corn grain in storage. This research was conducted in the Laboratory Plant Pest, Faculty of Agriculture, University of Riau using a completely randomized design with 6 treatments and 4 replications. Each experimental unit consisted of 10 Sitophilus zeamais M. in each soursop leaf powder 0% (0 g/100 g corn grain), 2% (2 g/100 g corn grain), 4% (4 g/100 g corn grain), 6% (6 g/100 g corn grain), 8% (8 g/100 g corn grain), 10% (10 g/100 g corn grain). Data were analyzed statistically by analysis of variance and least significant difference test at the advanced level of 5%. The results showed that the concentration of soursop leaf powder 10% (10 g/100 g corn grain) is more effective in controlling pest Sitophilus zeamais M. due cause total mortality of 92,5%, the early death for during 79,25 hours and lethal time 50 during 242,5 hours. Keywords: corn (Zea mays L.), weevil maize (Sitophilus zeamais M.), plant soursop (Annona muricata L.)